Mejora escolar y modelos de liderazgo: hacia la comprensión de un liderazgo efectivo (School improvement and leadership models: towards the understanding of an effective leadership) - Bush, Tony (Revista Eletrônica de Educação, 2019)
After giving an overview of the different approaches to school leadership and highlighting their strengths and weaknesses, the author warns about the one-dimensional approach of the different lines. He emphasizes that, given the complex and unpredictable educational context, it is not recommended to adopt a single approach for “all events” and recommends that leaders be able to distinguish each situation and adopt the most appropriate leadership response to each context. The careful reading and adaptation to the reality of each school is a key sign of any leadership process, given that “there is no one size that fits all”. Resumo Após dar uma visão panorâmica dos diferentes enfoques sobre liderança escolar e destacar os pontos fortes e fracos de cada um, o autor adverte sobre a abordagem unidimensional das diferentes linhas. Enfatiza que, dado o complexo e imprevisível contexto educacional, não é aconselhável adotar uma única abordagem de “todos os eventos” e recomenda que os líderes possam distinguir cada situação e adotar a resposta de liderança mais apropriada para cada contexto. A leitura cuidadosa e a adaptação à realidade de cada escola é um sinal chave de qualquer processo de liderança, uma vez que “não há medidas que se ajustem a todos os tamanhos”. Resumen Tras dar cuenta de una visión panorámica de los distintos enfoques de liderazgo escolar y destacar en cada uno fortalezas y debilidades, el autor advierte sobre el aporte unidimensional de los distintos acercamientos. Subraya que, dado lo complejo e impredecible del contexto educativo, no es aconsejable adoptar un solo enfoque “a todo evento” y recomienda que los líderes sean capaces de descifrar cada situación y adoptar la respuesta de liderazgo más adecuada a cada contexto. La atenta lectura y adaptación a la realidad de cada escuela es señal clave de todo proceso de liderazgo, dado que “no hay una medida que sirva para todas las tallas.” Keywords: School leadership, School context. Palavras-chave: Liderança escolar, Contexto escolar. Palabras claves: Liderazgo escolar, Context educativo. References BEGLEY, P. Editorial introduction: Cross-cultural perspectives on authentic school leadership”, Educational Management, Administration and Leadership, 35 (2), 2007, pp. 163-164. BENNETT, N.; HARVEY; J.; WISE, C.; WOODS, P. Distributed leadership: A Desk study. Nottingham: NCSL, 2003. BOTTERY, M. The challenges of educational leadership. London: Paul Chapman, 2004. BUSH, T. From management to leadership: semantic or meaningful change?, Educational Management, Administration and Leadership, 36 (2), 2008, pp. 271-288. BUSH, T. Theories of educational management: Fourth Edition. Londres: Sage, 2011. BUSH, T. Instructional leadership and leadership for learning: Global and South African Perspectives, Education as Change, 17 (S1), 2013, pp. 5-20. BUSH, T.; GLOVER, D. School leadership: Concepts and evidence. Nottingham: National College for School Leadership, 2003. BUSH, T.; GLOVER, D. Distributed leadership in action: Leading high performing leadership teams in English schools, School Leadership and Management, 32 (1), 2012, pp. 21-36. BUSH, T.; GLOVER, D. School leadership and management: What do we know, School Leadership and Management, 34 (5), 2014, pp. 553-571. BUSH, T.; GLOVER, D. School leadership in West Africa: Findings from a systematic literature review, Africa Education Review, 13 (3-4), 2016, pp. 80-103, DOI: 10.1080/18146627.2016.1229572 BUSH, T.; DUKU, N.; KOLA, S.; KIGGUNDU, E.; MOOROSI, P.; MSILA, V. The Zenex ACE School Leadership Research: Final Report. Pretoria: Department of Education, 2009. BUSH, T.; ODURO, G. New principals in Africa: Preparation, induction and practice, Journal of Educational Administration, 44 (4), 2006, pp. 359-375. CHIRICHELLO, M. Building capacity for change: Transformational leadership for school principals, artículo presentado en la conferencia de la ICSEI, enero, San Antonio, 1999. CRAWFORD, M. Solo and distributed leadership: Definitions and dilemmas, Educational Management, Administration and Leadership, 40 (5), 2012, pp. 610-620. DAY, C.; HARRIS, A.; HADFIELD M. Challenging the orthodoxy of effective school leadership, International Journal of Leadership in Education, 4 (1), 2001, pp. 39–56. DAY, C.; SAMMONS, P.; HOPKINS, D.; HARRIS, A.; LEITHWOOD, K.; GU, Q.; BROWN, E. Ten strong claims about successful school leadership. Nottingham: NCSL, 2010. FITZGERALD, T.; GUNTER, H. Contesting the orthodoxy of teacher leadership, International Journal of Leadership in Education, 11 (4), 2008, pp. 331-341. FROST, D. Teacher leadership: values and voice, School Leadership and Management, 28 (4), 2008, pp. 337-352. FULLAN, M. Successful school improvement. Buckingham: Open University Press, 1992. GRONN, P. Where to next for educational leadership?. In: BUSH, T.; BELL, L.; MIDDLEWOOD, D. (Eds.), The principles of educational leadership and management. Londres: Sage, 2010. GUNTER, H. Labels and labelling in the field of educational leadership, Discourse – Studies in the Cultural Politics of Education, 25 (1), 2004, pp. 21-41. HALLINGER, P. The evolving role of American principals: from managerial to instructional to transformational leaders, Journal of Educational Administration, 30 (3), 1992, pp. 35-48. HALLINGER, P. Leading educational change: Reflections on the practice of instructional and transformational leadership, Cambridge Journal of Education, 33 (3), 2003, pp. 329-350. HALLINGER, P. (forthcoming), Bringing context out of the shadows of leadership, Educational Management, Administration and Leadership. HALLINGER, P.; HECK, R. Leadership for learning: Does collaborative leadership make a difference in student learning?. Educational Management, Administration and Leadership, 38 (6), 2010, pp. 654-678. HARGREAVES, A. Inclusive and exclusive educational change: Emotional responses of teachers and implications for leadership, School Leadership and Management, 24 (3), 2004, pp. 287-306. HARRIS, A. Distributed leadership in schools: leading or misleading?, Educational Management, Administration and Leadership, 32 (1), 2004, pp. 11-24. HARRIS, A. Distributed leadership. In: DAVIES, B. (Ed.). The essentials of school leadership. Londres: Paul Chapman, 2005. HARRIS, A. Distributed leadership: Current evidence and future directions. In: BUSH, T.; BELL, L.; MIDDLEWOOD, D. (Eds.). The principles of educational leadership and management. Londres: Sage, 2010. HARTLEY, D. Paradigms: How far does research in distributed leadership “stretch”, Educational Management, Administration and Leadership, 38 (3), 2010, pp. 271-285. HELTERBRAN, V. R. “Teacher leadership: Overcoming ‘I am just a teacher’ syndrome”, Education, 131 (2): 363-371, 2010). HOYLE, E.; WALLACE, M. Educational leadership: Ambiguity, professionals and managerialism. Londres: Sage, 2005. LAMBERT, L. New directions in the preparation of educational leaders, Thrust for Educational Leadership, 24 (5), 1995, pp. 6-10. LAMBERT, L. A framework for shared leadership, Educational Leadership, 59 (8), 2002, pp. 37-40. LAW, E. Distributed curriculum leadership in action: A Hong Kong case study, Educational Management, Administration and Leadership, 38 (3), 2010, pp. 286-303. LEITHWOOD, K. Leadership for school restructuring, Educational Administration Quarterly, 30 (4), 1994, pp. 498–518. LEITHWOOD, K.; JANTZI, D.; STEINBACH, R. Changing leadership for changing times. Buckingham: Open University Press, 1999. LEITHWOOD, K.; DAY, C.; SAMMONS, P.; HARRIS, A.; HOPKINS, D. Seven strong claims about successful school leadership. Londres: DfES, 2006. LUMBY, J. Collective leadership of local school systems: power, autonomy and ethics, Educational Management, Administration and Leadership, 37 (3), 2009, pp. 310-328. LUMBY, J. Distributed leadership: The uses and abuses of power, Educational Management, Administration and Leadership, 41 (5), 2013, pp. 581-597. MACBEATH, J.; DEMPSTER, N. Connecting leadership and learning. Londres: Routledge, 2009. MILLER, T.; MILLER, J. Educational leadership in the new millennium: A vision for 2020, International Journal of Leadership in Education, 4 (2), 2001, pp. 181-189. MORGAN, G. Images of organization. Newbury Park, CA: Sage, 1997. MUIJS, D.; HARRIS, A. Teacher leadership in (in)action: Three case studies of contrasting schools, Educational Management, Administration and Leadership, 35 (1, 2007, pp. 11-134. RHODES, C.; BRUNDRETT, M. Leadership for learning. In: BUSH, T.; BELL, L.; MIDDLEWOOD, D. (Eds.). The principles of educational leadership and management. Londres: Sage, 2010. ROBINSON, V. School leadership and student outcomes: Identifying what works and why. Winmalee, New South Wales: Australian Council of Leaders, 2007. SERGIOVANNI, T. J. The principalship: A reflective practice perspective. Needham Heights, MA: Allyn Bacon, 1991. SOUTHWORTH, G. School leadership and school development: reflections from research, School Organisation, 12 (2), 1993, pp. 73–87. STEVENSON, H. Teacher leadership as intellectual leadership: Creating spaces for alternative voices in the English school system, Professional Development in Education, 38 (2), 2012, pp. 345-360. THOONEN, E.; SLEEGERS, P.; OORT, F.; THEA, T. D.; PEETSMA, T.; FEMKE, P.; GEIJSEL, P. How to improve teaching practices: The role of teacher motivation, organizational factors and leadership practices, Educational Administration Quarterly, 47 (3), 2011, pp. 496-536. TIMPERLEY, H. Distributed leadership: Developing theory from practice, Journal of Curriculum Studies, 37 (4), 2005, pp. 395-420. WEST-BURNHAM, J. Leadership for learning: Re-engineering “mind sets”, School Leadership and Management, 17 (2), 1997, pp. 231-243. WOODS, G. The “bigger feeling” the importance of spiritual experience in educational leadership, Educational Management, Administration and Leadership, 35 (1), 2007, pp. 135-155. WOODS, P. Authenticity in the bureau-enterprise culture: The struggles for authentic meaning, Educational Management, Administration and Leadership, 35 (2), 2007, pp. 295-320. YUKL, G. A. Leadership in organizations. 5a edición, Upper Saddle River, NJ: Prentice-Hall, 2002.